Phenotyping of light-activated neurons in the mouse SCN based on the expression of FOS and EGR1 - Riedel, Casper Schwartz; Georg, Birgitte; Hannibal, Jens (Frontiers in Physiology, 2024)
Light-sensitive neurons are located in the ventral and central core of the suprachiasmatic nucleus (SCN), whereas stably oscillating clock neurons are found mainly in the dorsal shell. Signals between the SCN core and shell are believed to play an important role in light entrainment. Core neurons express vasoactive intestinal polypeptide (VIP), gastrin-releasing peptide (GRP), and Neuroglobin (Ngb), whereas the shell neurons express vasopressin (AVP), prokineticin 2, and the VIP type 2 (VPAC2) receptor. In rodents, light has a phase-shifting capacity at night, which induces rapid and transient expression of the EGR1 and FOS in the SCN. The present study used immunohistochemical staining of FOS, EGR1, and phenotypical markers of SCN neurons (VIP, AVP, Ngb) to identify subtypes/populations of lightresponsive neurons at early night. Results: Double immunohistochemistry and cell counting were used to evaluate the number of SCN neurons expressing FOS and EGR1 in the SCN. The number of neurons expressing either EGR1 or FOS was higher than the total number of neurons co-storing EGR1 and FOS. Of the total number of light-responsive cells, 42% expressed only EGR1, 43% expressed only FOS, and 15% expressed both EGR1 and FOS. Light-responsive VIP neurons represented only 31% of all VIP neurons, and EGR1 represents the largest group of light-responsive VIP neurons (18%). VIP neurons expressing only FOS represented 1 % of the total light-responsive VIP neurons. 81% of the Ngb neurons in the mouse SCN were light-responsive, and of these neurons expressing only EGR1 after light stimulation represented 44%, whereas 24% expressed FOS. Although most light-responsive neurons are found in the core of the SCN, 29% of the AVP neurons in the shell were light-responsive, of which 8% expressed EGR1, 10% expressed FOS, and 11% co-expressed both EGR1 and FOS after light stimulation. Conclusion: Our analysis revealed cell-specific differences in light responsiveness between different peptidergic and Ngb-expressing neurons in different compartments of the mouse SCN, indicating that light activates diverse neuronal networks in the SCN, some of which participate in photoentrainment.